Membangun Kesadaran Keamanan Digital melalui Permainan Serius: Studi Komparatif Visual Novel dan Quiz Mini Game pada Siswa SMP - Tony Tan; Febrianto Febrianto; Ricky Jong; Tony Wibowo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Digital security awareness is an essential competency for students in dealing with online risks. This study aims to compare the effectiveness of two serious game genres, namely visual novel and quiz mini game, in improving digital security awareness among junior high school students. A descriptive qualitative approach with descriptive quantitative support was employed, involving 27 students from a single junior high school class. The research procedure included a pre-test, gameplay sessions of a visual novel (approximately 20 minutes) and a quiz mini game (approximately 15 minutes), a post-test, and semi-structured interviews. Pre-test and post-test data were analyzed descriptively, while interview data were examined using thematic analysis. The results indicate that visual novels are more effective in fostering conceptual understanding through contextual narratives, whereas quiz mini games are more effective in enhancing learning motivation through interactive challenges. These findings suggest that a hybrid learning model combining both genres has the potential to optimize students’ conceptual understanding and learning motivation in digital security education.